Fish Swimming Behavior and Strategies Under Different Hydrodynamic Conditions in Fishways with Various Vertical Slot Configurations - Ouyang, Lijian; Li, Dongqiu; Cui, Shihao; Wu, Xinyang; Liu, Yang; Han, Xiaowei; Zhou, Shengzhi; Xu, Gang; Tu, Xinggang; Chen, Kang; Gualtieri, Carlo; Yao, Weiwei (Fishes, 2025)
Vertical slot fishways are a crucial measure to mitigate the blockage of fish migration caused by hydraulic engineering infrastructures, but their passage efficiency is often hindered by the complex interactions between fish behavior and hydrodynamic conditions. This study combines computational fluid dynamics (CFD) simulations with behavioral laboratory experiments to identify the hydrodynamic characteristics and swimming strategies of three types of fishways—Central Orifice Vertical Slot (COVS), Standard Vertical Slot (SVS), and L-shaped Vertical Slot (LVS)—using the endangered species Schizothorax prenanti from the upper Yangtze River as the study subject. The results revealed that (1) a symmetric and stable flow field was formed in the COVS structure, yet the passage ratio was the lowest (50%); in the SVS structure, high turbulent kinetic energy (peak of 0.03 m2/s2) was generated, leading to a significant increase in the fish’s tail-beat angle and amplitude (p < 0.01), with the passage time extending to 10.2 s. (2) The LVS structure induced a controlled vortex formation and created a reflux zone with low turbulent kinetic energy, facilitating a “wait-and-surge” strategy, which resulted in the highest passage ratio (70%) and the shortest passage time (6.1 s). (3) Correlation analysis revealed that flow velocity was significantly positively correlated with absolute swimming speed (r = 0.80), turbulent kinetic energy, and tail-beat parameters (r > 0.68). The LVS structure achieved the highest passage ratio and shortest transit time for Schizothorax prenanti, demonstrating its superior functionality for upstream migration. This design balances hydrodynamic complexity with low-turbulence refuge zones, providing a practical solution for eco-friendly fishways.